2013
DOI: 10.1002/ldr.2261
|View full text |Cite
|
Sign up to set email alerts
|

Organic Carbon and Nitrogen Associated with Soil Aggregates and Particle Sizes Under Different Land Uses in Tigray, Northern Ethiopia

Abstract: Soil aggregation serves as storage and cycling of soil organic carbon (SOC) and total nitrogen (TN), which are essential for the functioning of terrestrial ecosystems. Thus, aggregate and particle associated SOC and TN in 0‐ to 10‐cm and 10‐ to 20‐cm layers were estimated for five land uses: rainfed cultivation (RF), agroforestry (AF), open pasture (OP), silvopasture (SP), and irrigation (IR) each with five replications within a watershed in Ethiopia. OP had the highest WSA > 2 mm (88·7%) and SOC associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
124
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(140 citation statements)
references
References 68 publications
(104 reference statements)
13
124
1
2
Order By: Relevance
“…Addition of more organic matter from leaf and root litters from the F. albida trees in AF than the other land uses likely explains the improved WSA in AF [36]. Similarly, a study by Gelaw et al [37] at the same site found that soils under natural grazing lands adjacent to cultivated lands were well structured, and contained higher SOC concentrations.…”
Section: Soil Physical Quality Indicatorsmentioning
confidence: 84%
See 1 more Smart Citation
“…Addition of more organic matter from leaf and root litters from the F. albida trees in AF than the other land uses likely explains the improved WSA in AF [36]. Similarly, a study by Gelaw et al [37] at the same site found that soils under natural grazing lands adjacent to cultivated lands were well structured, and contained higher SOC concentrations.…”
Section: Soil Physical Quality Indicatorsmentioning
confidence: 84%
“…However, the difference among land uses was not statistically significant. Similarly, the detrimental effects of tillage may have offset the beneficial effects of SOC on TP [17,32,37]. …”
Section: Soil Physical Quality Indicatorsmentioning
confidence: 99%
“…60% and 40% of total SOC of surface soil layers in Bavarian forests and grasslands, respectively. Several other studies have reported significant (>20%) contributions of >20 µm SOC to total SOC in various systems such as agricultural temperate soils 10 (Balesdent et al, 1998;Besnard et al, 2001) or cultivated tropical soils (Barthes et al, 2008;Gelaw et al, 2015). Moreover, several authors observed that increases in SOC stocks following a land management change were mostly due to an increase in sand-size particulate organic matter (e.g.…”
Section: The Carbon Saturation Of Fine Soil Particles Is Not Relevantmentioning
confidence: 96%
“…Munoz-18 Rojas et al 2012;De Moraes Sá et al 2013;Gelaw et al 2013;Parras-Alcántara et al 2013, 201419 Srinivasarao et al 2014;Yu and Jia 2014;Behera et al 2015;Peng 2015). Agriculture can strongly 20 limit SOM accumulation, influencing soil aggregate formation and turnover (Jastrow 1996;Cerdà, 21 2000;Jacobs et al 2010;Gosling et al 2013).…”
Section: Introductionmentioning
confidence: 99%